Needs Analysis of Physics Learning Media Development - Achmad Ridho Khuzaini (Universal Education, 2024)
Learning media is one of the important aspects in physics learning. This research aims to analyze the needs of physics learning media development. The research was conducted in four high schools in Malang Regency. We have distributed questionnaires to 9 physics teachers and 143 students. The questionnaire for students consists of three aspects, namely student response, learning experience, and media needs. The questionnaire for teachers consisted of two aspects, namely experience in learning, and media needs. The results of this study show that learning still needs innovative media development, one of which is Lectora Inspire-based media. Lectora Inspire-based media has several advantages that will be discussed in this article.